In vitro and in silico evaluation of the antimicrobial potential of Celtis zenkeri roots volatile metabolites - Okpala, Ejike Onwudiegwu; Anthony, William Ojoniko; Eneogwe, Godfrey Okechukwu; Odeja, Oluwakayode Olubunmi; Ibok, Michael Gabriel; Onoja, Joel Ojogbane; Odewo, Samuel Akinniyi; Ike, Shedrach Ndubuisi; Onanuga, Olusimbo Adesegun; Semire, Banjo (Eclética Química, 2024)
This study is aimed at investigating the volatile constituents of the air-dried roots of Celtis zenkeri. The volatile oil was extracted using hydro-distillation method and characterised using gas chromatography-mass spectrometry (GC-MS). The volatile oil was screened against six selected bacteria and four fungi strains using the agar diffusion method. The molecular docking study of the identified compounds was conducted to investigate their binding pattern with the substrate and nucleotide complexes of Enterococcus faecium aminoglycoside-2’’-phosphotransferase-IIa [APH(2’’)-IIa] (PDB ID: 3HAM) and full-length Lanosterol 14 alpha-Demethylases of Prominent fungal pathogens Candida albicans (PDB ID: 5V5Z). The yield of the volatile oil (% w/w) root of C. zenkeri was 0.79%. Six compounds were identified in the root essential oil representing 80.07% of the volatile oil. 2-methyl-1-pentene (40.01%) was the most abundant compound in the root essential oil. The volatile oil from roots of the C. zenkeri exhibited good activity against all the screened bacteria and fungi strains at a concentration of 12.5-100 mg/mL when compared with Gentamicin for bacteria and Tioconazole for fungi.